Διερεύνηση της επίδρασης της φωτοδιάσπασης στην διάσπαση φαρμακευτικών ενώσεων και ενδοκρινικών διαταρακτών στο υδάτινο περιβάλλον - Στρατογιάννη, Γεωργία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Υδατικών Πόρων και Περιβάλλοντος, 2014)
The purpose of this thesis is to investigate the effects of photodegradation during decomposition of pharmaceutical compounds such as diclofenac (DCF), ibuprofen (IBF), naproxen (NPX), ketoprofen (KFN) and of endocrine disrupters such as triclosan (TCS), bisphenol A (BPA), nonylphenol (NP), nonylphenol monoethoxylate (NP1EO) and nonylphenol diethoxylate (NP2EO) through the implementation of sunlight on ultra-pure water. These experiments were performed at the Sanitary Engineering Laboratory of The National Technical University of Athens. An in-depth description of the studied substances is being made but also a bibliographical review of their concentrations to their way outs from sewage treatment plants, in sludge and in surface and ground waters as well. There is also reference to bibliographical data that resulted from other studies. What follows is a description of modes of function concerning devices, measuring instruments and of the experimental protocols which were used for the composition of this thesis. To begin with, what was studied was the implementation of solar radiation on ultra-pure water which had been previously vaccinated with the tested substances. The experimental data during photodegradation resulted to the rates of photolysis and half-life for the tested substances. Moreover, controlling experiments of hydrolysis were conducted at 3 different pH scales (6, 7 and 8) on the tested substances. In combination with the respective results on radiated samples that postgraduate student Eutaxias Alexandros had collected during his experimental procedure, half-lives and rates of photodegradation were derived. The thesis ends with the synopsis of the most important conclusions that evoked from the analysis of the experimental results.